INTERACTIONS IN CONVERSATIONS BETWEEN THREE PEOPLE IN PODCAST: A STUDY OF PRAGMATICS - Ricka Putri Suteja (Universitas Islam Sumatera Utara (UISU), 2021)
The interaction process between each party can affect the course of the conversation. This study aims to investigate the characteristics of podcast conversations and the communication style used between two interviewers and one resource person in Catatan Psikologi's podcast entitled Quarter Life Crisis. This study used qualitative methods with a conversational analysis (CA) approach as well as collaborative communication and competitive communication theories. The process of conversations transcription used the conventions written by Du Bois. The results showed minimal response phenomena, interruptions, and overlaps in the conversation, leading to collaborative communication both at the word and sentence. However, the collaborative communication style has a more significant emergence. Based on the analysis above, the parties involved in the communication tried to build togetherness and cooperation which can be seen in the narrative. When one speaker told a story, the others also participated in the conversation by providing minimal responses, showing sympathy, and also comments or opinions.